2019
DOI: 10.21615/cesmvz.14.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de Rinotraqueítis Infecciona Bovina (BHV-1) en el municipio de Toca, Boyacá

Abstract: Introducción. La Rinotraqueítis Infecciosa Bovina (RIB) es una enfermedad infectocontagiosa que afecta principalmente a bovinos y bufalinos, encontrándose ampliamente distribuida a nivel mundial, siendo una de las principales causas de perdidas económica y físicas en las producciones. Objetivo. determinar la prevalencia de la Rinotraqueítis Infecciosa Bovina (BHV-1) en el municipio de Toca, Boyacá. Materiales y métodos. Se recolectaron 350 muestras de sangre Bovina, las cuales fueron procesadas en el laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
3
1
Order By: Relevance
“…Holstein and Ayrshire had the highest seroprevalences among the evaluated breeds; this finding is similar to that reported by Ortíz-González et al [12]. However, Sibhat et al [25] have reported that the Jersey breed and crosses of Holstein-Friesian by Zebu have the highest seroprevalences of 62% and 41.8%, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Holstein and Ayrshire had the highest seroprevalences among the evaluated breeds; this finding is similar to that reported by Ortíz-González et al [12]. However, Sibhat et al [25] have reported that the Jersey breed and crosses of Holstein-Friesian by Zebu have the highest seroprevalences of 62% and 41.8%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…In Sotaquirá, a significant statistical association was found with the presentation of abortions in herds, which is in agreement with the findings of Mahajan et al [37]. A statistical association between the presence of abortion and the disease was reported but differed from the observation made by Ochoa et al [11] and Ortíz-González et al [12], who did not report this relationship with abortion. In addition, gestation in virus-infected cattle can be carried to term with the birth of dead calves or calves that died shortly after birth or within the first 2 weeks [38].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations